Consumer Evaluations Of Beautification Products: Effects Of Extrinsic Cues - Parvin, Nargis; Kabir Chowdhury, Md. Humayun (Asian Academy of Management (AAM), 2006)
This study investigates the influence of extrinsic cues, i.e. brand image, perceived price, perceived quality, and perceived country of origin on consumers' evaluative judgments for beautification products. Multi-item measures were used for data collection. Results revealed that three extrinsic cues: brand image, perceived quality, and perceived country of origin have positive and significant influence on consumers' brand evaluation of beautification brands. Only perceived price has shown no such influence on consumers' brand evaluation. Finally, unanswered questions and future research directions are presented.